Analysis of The Effect of Discount Prices, Customer Reviews and Electronic Word of Mouth on Purchase Decisions - Setyawati, Eka Ayu; Murniningsih, Rochiyati; Santoso, Mulato (Prosiding University Research Colloquium, 2022)
The study aims to test the effect of discounted prices, customer reviews and electronic word of mouth on purchase decisions at Shopee. This research sample is the people of Magelang Regency Shopee users and at least have done transactions shopee. The data retrieval method uses purposive sampling with non-probability sampling techniques with a sample number of 100 respondents. The tool used is a multiple linear regression analysis tool with the help of SPSS. The results of this study showed that discount prices had a positive effect on purchasing decisions, customer reviews had no effect on purchasing decisions, and electronic word of mouth had a positive effect on purchasing decisions.